Abusive supervision and counterproductive work behaviors under generational differences: a chain mediation model between perception of organizational politics and defensive silence - Qiu, Ailin; Li, Zhaoqi; Choi, MyeongCheol; Kim, Hann Earl (Frontiers in Psychology, 2025)
Abusive supervision leads to employees' counterproductive work behaviors, which undermines an organization's sustainable development and survival. This study posits that the relationship between abusive supervision and counterproductive work behaviors varies across different age groups. Therefore, from the perspective of generational differences (Post-80s, Post-90s, Post-00s), we explored the mediating role of perceptions of organizational politics and defensive silence on abusive supervision and counterproductive work behaviors among 441 Chinese manufacturing employees by generation. The empirical analysis was conducted using Amos and SPSS statistical software. The results showed that abusive supervision significantly positively affected counterproductive work behaviors. Additionally, it finds that perceptions of organizational politics and defensive silence each serve as mediators in the relationship between abusive supervision and counterproductive work behaviors, forming a chained mediation effect. The study showed that the results differed among the Post-80s, Post-90s, and Post-00s groups. This suggests that generational differences have different perspectives on abusive supervision and counterproductive work behaviors. These results reveal the existence of a generational gap. The main contribution of this study lies in its identification of the chain mediating effects of perceptions of organizational politics and defensive silence between abusive supervision and counterproductive work behaviors from the perspective of generational differences for the first time. This enriches the research on generational differences, abusive supervision, and counterproductive work behaviors, providing new perspectives for future research endeavors.